Decentralized control of distributed energy resources in electric distribution grid - Zhang, Jiyue (Nanyang Technological University, 2022)
The high penetration of Distributed Energy Resources (DERs) in the distribution network has become an inevitable trend, bringing new challenges to the modelling, analysis and control of the grid due to DER's intermittent availability and varied operational strategies. Therefore, in order to achieve stable operation of distribution networks, it has become necessary to establish appropriate steady-state models of DERs and apply effective control strategies.